Gold standard diagnostic algorithm for the differential diagnosis of local allergic rhinitis - Krzych-Fałta, Edyta; Wojas, Oksana; Samoliński, Bolesław K.; Majsiak, Emilia; Białek, Sławomir; Lishchuk-Yakymovych, Khrystyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Local allergic rhinitis, defined as a localized allergic response of the nasal mucosa in the absence of systemic atopy, poses a considerable clinical issue due to its prevalence. The gold standard in local allergic rhinitis diagnostics is primarily the patient’s history taking and nasal allergen provocation testing or, alternatively, the basophil activation test, described as “an allergic reaction in a test tube”.